Core decompression and biotechnologies in the treatment of avascular necrosis of the femoral head. Issue 2 (21st February 2017) - Calori, Giorgio Maria; Mazza, Emilio; Colombo, Alessandra; Mazzola, Simone; Colombo, Massimiliano
Abstract : Avascular necrosis (AVN) of the femoral head (FH) causes 5% to 12% of total hip arthroplasties (THA). It especially affects active male adults between the third and fifth decades of life. The exact worldwide incidence is unknown. There are only few data related to each country, but most of it relates to the United States. Non-surgical management has a very limited role in the treatment of AVN of the FH and only in its earliest stages. Core decompression (CD) of the hip is the most common procedure used to treat the early stages of AVN of the FH. Recently, surgeons have considered combining CD with autologous bone-marrow cells, demineralised bone matrix or bone morphogenetic proteins or methods of angiogenic potential to enhance bone repair in the FH. Manuscripts were deemed eligible for our review if they evaluated treatment of early stage AVN of the FH with biotechnology implanted via CD. After application of eligibility criteria, we selected 19 reports for final analysis. The principal results showed that only by correctly mastering the therapeutic principles and adopting proper methods specifically oriented to different stages can the best therapeutic effect be achieved. Combining CD with biotechnology could result in a novel long-lasting hip- preserving treatment option. Furthermore, more refined clinical studies are needed to establish the effectiveness of biotechnology treatments in AVN of the FH. Cite this article: EFORT Open Rev 2017;2:41-50. DOI: 10.1302/2058-5241.2.150006